2016
DOI: 10.1002/ejlt.201500573
|View full text |Cite
|
Sign up to set email alerts
|

Toward determining fat quality parameters of fish oil by means of 1H NMR spectroscopy

Abstract: The consumption of fish oil-based dietary supplements has increased dramatically in recent years, which is mainly due to their high content of health promoting omega-3 fatty acids. However, these polyunsaturated fatty acids are extremely prone to oxidation. This study investigated the potential of 1 H NMR spectroscopy for the assessment of the oxidative deterioration of fish oils. Nine raw fish oils of different fish species were stored for 3 months at room temperature at different degrees of sunlight exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Additionally, parts of triglycerides previously used to measure oxidation were also included. These results again mimic previous high-field studies of fish oil oxidation. , …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, parts of triglycerides previously used to measure oxidation were also included. These results again mimic previous high-field studies of fish oil oxidation. , …”
Section: Resultssupporting
confidence: 90%
“…Similar peaks have been used in modeling of fish oil and DHA oxidation using high-field NMR. 6,8 The linear model was able to predict the PV more accurately than PLSR, with a higher R 2 value and lower error. The PLSR model included more integral bins than the linear model.…”
Section: ■ Experimental Proceduresmentioning
confidence: 93%
See 2 more Smart Citations
“…Considering this, the R 2 value of 0.99 was quite favorable for quantification model in this research. Giese reported PLSR model was used to predict PV, AnV, TOTOX, and AV in fish oil by 1 H NMR spectra and the best regression models reached an R 2 of 0.949, 0.962, 0.991, and 0.977, respectively. Zhang reported that the PLS models performed better than the PCR models in quantitative prediction of AV of edible oils by UV–vis spectrometry, with R 2 values of 0.9904–0.9977.…”
Section: Resultsmentioning
confidence: 99%